Giant cyst of the antecubital fossa in a female patient with rheumatoid arthritis (A case report) - A. A. Roskidailo (Современная ревматология, 2018)
The paper describes a case of rheumatoid arthritis in a 58-year-old female patient who sought medical advice for complaints of a massive soft tissue tumor upon the anterior and lateral surfaces of the left elbow joint. Left elbow bursitis was suspected. Magnetic resonance imaging showed a relationship between the massive tumor (anastomoses) and the joint. A surgical intervention was undertaken. A cyst consisting of two components was excised; anterolateral synovectomy and plastic surgery of the anterior elbow joint capsule were performed. The patient was examined 6 months later; the result was satisfactory.